COMMON DISCOURSE PATTERNS OF EDUCATIONAL RESEARCH ARTICLE ABSTRACTS - I Gede Bagus Wisnu Bayu Temaja; Gusti Ayu Gede Sukraningsih (STKIP PGRI Jombang, 2021)
The previous study already conducted a similar study in several fields, except education, thus, this study was conducted to complete it. This study aimed at investigating discourse patterns of research article abstracts in the education discipline. The data were a set of research article abstracts of five sub-disciplines in education, i.e., language education, mathematics and natural science education, social education, technological education, and elementary education. The data were collected from journals of education study. This research was conducted by implementing a four-move abstract structure. The results found that Moves 1 (research space), 2 (research procedure), and 3 (result summary) were obligatory, while Move 4 (result evaluation) was considered an optional move. The most common pattern discovered was 1-2-3. The pattern of 1-2-3-4 is another common pattern obtained, except for social education. These results provide the discourse patterns of educational research article abstracts and are regarded as new findings in the previous and related studies.